2016
DOI: 10.3389/fpls.2016.01645
|View full text |Cite|
|
Sign up to set email alerts
|

Seed Embryo Development Is Regulated via an AN3-MINI3 Gene Cascade

Abstract: In agriculture, seed mass is one of the most important components related to seed yield. MINISEED3 (MINI3) which encodes the transcriptional activator WRKY10, is thought to be a pivotal regulator of seed mass. In Arabidopsis SHORT HYPOCOTYL UNDER BLUE1 (SHB1) associates with the promoter of MINI3, regulating embryo cell proliferation (both cell division and elongation), which, in turn, modulates seed mass. Furthermore, the recruitment of SHB1 via MINI3 to both its cognate promoter and that of IKU2 implies a tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 42 publications
(107 reference statements)
2
27
0
Order By: Relevance
“…In addition, GIF1 was reported to play significant roles in leaf, flower, and root development in Arabidopsis [8][9][10][11][12][13][14] , indicating that GIF1 is required for normal plant organ growth. Surprisingly, a previous study showed that one mutant allele of GIF1 (an3) promotes seed growth 48 . In this study, we have sufficient evidence to support that GIF1 is a positive regulator of seed size in Arabidopsis.…”
Section: Articlementioning
confidence: 95%
“…In addition, GIF1 was reported to play significant roles in leaf, flower, and root development in Arabidopsis [8][9][10][11][12][13][14] , indicating that GIF1 is required for normal plant organ growth. Surprisingly, a previous study showed that one mutant allele of GIF1 (an3) promotes seed growth 48 . In this study, we have sufficient evidence to support that GIF1 is a positive regulator of seed size in Arabidopsis.…”
Section: Articlementioning
confidence: 95%
“…Condition of Arabidopsis plant growth was described by Meng and Yao (2015) and Meng L. et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…The seedlings grown on agar were maintained in a growth room under 16 hr/8 hr light/dark cycles with 21°C ± 2°C. Plants grown in soil less media were maintained in a controlled environment growth room under 16 hr/8 hr light/dark cycles with 21°C ± 2°C (Meng, Li, Liu, & Jiang, 2016;Meng, Wang, et al, 2016;Meng, Wang, Yao, & Liu, 2015a, Meng, Wang, Yao & Liu, 2015b.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Besides the delay of an3 stomatal development, an3 mutants present many developmental delays, for example, narrower and smaller leaf blades (Horiguchi et al, 2005), smaller cell number in leaf blades (Meng, Wang, et al, 2016). However, an3 mutants have longer primary roots, more lateral roots, and larger seed mass than does wild type (Meng, Xu, et al, 2017;Meng & Yao, 2015).…”
Section: An3 Is a Novel Positive Regulator Of Stomatal Developmentmentioning
confidence: 99%
See 1 more Smart Citation